The dual vocational training in the Law Field from teachers and students’ perspectives: Constraints and success keys in a Cuban university - Silva González, Jorge Luis; Ulloa Guerra, Oscar; Martínez Sierra , Ricel; Sartor Harada , Andresa (Revista Pedagogía Universitaria y Didáctica del Derecho, 2022)
The dual professional training of Law students has been inserted from the 2018-2019 school year in Cuba. Since then it has been a priority in the educational policy of Higher Education, which is manifested in the different institutions that make up the legal sector. In this sense, the present study aims to assess -from the theoretical, legal and practical point of view- the development of the dual training process of the students of the Law career in Cuba, based on the experience of the province of Pinewood of the river. For this, with the use of analysis-synthesis, induction-deduction methods and bibliographic review, the theoretical-conceptual references on professional training are systematized, with emphasis on dual training, the legal norms that support said training are analyzed. training through a fixed-term employment contract and part of the results obtained from practical experience are exposed.